0897 Low Stability In Rest Activity Rhythms Is Associated With Higher Suicidal Ideation In Adolescents With Bipolar Disorder. (12th April 2019) - Chen, Qianyi; Franzen, Peter; Goldstein, Tina; Gratzmiller, Sarah
Abstract: Introduction: Previous research has shown consistent evidence of disturbed sleep among youth with bipolar disorder (BP). Decreased need for sleep is a symptom of mania, while insomnia and hypersomnia characterize depressive episodes. Further, sleep disturbance has been consistently linked with suicide, and youth with BP are among the group at highest risk for suicide. Methods: Youth (age 12-22) with (n=37) and without (n=26) bipolar I, II, or NOS disorder wore an Actiwatch Spectrum Plus to estimate daily rest-activity rhythms (RARs) over 2 weeks (mean=14.8 days). Depressive symptoms and suicidal ideation were measured with the Mood Feelings Questionnaire (MFQ) and Suicidal Ideation Questionnaire (SIQ) scales. We examined three non-parametric parameters derived from the minute-by-minute activity counts: interdaily stability (IS), consistency of activity across successive days; intradaily variability (IV) of activity; and relative amplitude (RA), the relative difference between most active 10 and least active 5 hours. IS, IV, and RA were compared across groups, and within the BP group, the associations between RARs and MFQ and SIQ were examined. Results: RARs did not differ between the BP and Control groups (p's > .25). In the BP group, youth with lower IS and higher RA reported more suicidal ideation (r=-0.69, p<0.001; r=.468, p<.009). Lower IS was also associated with more depressive symptoms (r=-0.405, p < .03). Conclusion: Youth with BP who exhibited less consistent 24-hour rest-activity rhythms concurrently reported greater suicidal ideation and more depressive symptoms. Prospective evidence is needed to confirm the direction of these associations. Irregular sleep-wake patterns are a modifiable risk factor. Interventions targeting these factors may therefore help reduce suicidality in high-risk youth. In addition, platforms to provide real-time feedback of activity patterns to patients/clinicians could be developed. Support (If Any): Funded in part by the American Foundation for Suicide Prevention and the University of Pittsburgh Clinical and Translational Science Institute